Tailoring the delivery of cancer diagnosis to adolescent and young adult patients displaying strong emotions: An observational study of two cases - Live Korsvold (International Journal of Qualitative Studies on Health & Well-Being, 2016)
Delivering the bad news of a cancer diagnosis to adolescent and young adult (AYA) patients who display strong emotions is particularly challenging not the least because AYAs are at a vulnerable developmental stage. Due to the lack of research on how to personalize the delivery of bad news to AYA patients’ emotions we report a case study of the communicative behavior of oncologists in two such consultations to describe the complexity of the phenomena at study. We audio-recorded and transcribed consultations where oncologists delivered cancer diagnoses to nine AYAs aged 12–25 years. Two of these patients displayed particularly strong emotional behavior (anger, fear, and sadness) and were chosen as cases. An interpretative analysis in three steps was applied to investigate the oncologists’ communicative behavior when delivering bad news. The focus was on how the oncologists responded to the strong but different emotional behaviors of the AYAs. We also related the oncologists’ communicative behavior to elements from a widely used protocol for delivering bad news. We found that the oncologists applied five communication strategies: elicit patient perspective, provide information, respond to patient's expression of emotion (acknowledging and containing emotions), encourage commitment to treatment, and provide hope. The findings illustrate how oncologists’ communicative behavior may be tailored to individual expressions of emotions in AYA cancer patients.